POPULASI AEDES SP YANG DOMINAN SEBAGAI VEKTOR POTENSIAL DENGUE DI KOTA JAMBI - Suhermanto Suhermanto; Susy Ariyani (Poltekkes Kemenkes Jambi, 2019)
Summary Jambi City is still the highest contributor of dengue sufferers from 11 regencies/cities in Jambi Province. The target of controlling the Aedes sp mosquitoes has not been selectively carried out yet because there is no information regarding the diversity of populations and the characteristics of breeding place for Aedes sp in endemic areas of dengue in Jambi City. The problems examined about the dominant dengue potential vector and the type of breeding place. So the purpose of this study was to know the dominant population between Ae. aegypti and Ae. albopictus which was caught with an Aspirator Backpack and its characteristic of breeding place. The research method was descriptive with the approach of exploration studies for Aedes sp mosquitoes in the 5 highest sub-districts of DHF rate. The amount of samples were 100 houses every village which selected by random sampling. The results of the study stated that Aedes albopictus was found more dominantly, the highest ratio of Aedes albopictus mosquitoes were in the Lingkar Selatan Village with a ratio of (11: 1), and The Kenali Besar Village with a ratio of 9: 1. The same thing with the ratio of Aedes albopictus larvae, there were 3 sub-districts located on the suburbans of Jambi City, they were Kenali Besar Village, Talang Bakung Village and Lingkar Selatan Village. The villages had a ratio of Aedes albopictus larvae six times greater than the ratio of aedes albopictus in villages where not in the suburban of Jambi City. This study also found that the baths (47%) and drums (28.5%) were the largest breeding sites for Aedes sp larvae. The researcher expected that there will be a further research about the percentage of Aedes sp which are infected with the dengue virus so it can prove that Aedes albopictus is the main vector of DHF in Jambi City.